Sonochemical reactors: Review on features, advantages and limitations - Asgharzadehahmadi, S.; Abdul Raman, Abdul Aziz; Parthasarathy, R.; Sajjadi, B. (Elsevier, 2016)
Sonochemical reactors operate based on the release of high amount of energy from ultrasonic irradiations. More application in chemical processes are being developed using these reactors. But the potential of their applications are still limited largely due to the lack of understanding about their design, operational and performance characteristics. A detail review is therefore conducted on available literature in this paper. From the review, the design features of sonochemical reactors are defined by different types, number and position of ultrasonic transducers, whereas their operational parameters are determined by ultrasonic frequency and intensity. As in the case of stirred vessel, sonochemical reactors can be also characterized for their performance based on mass transfer, mixing time and flow pattern. The review claims that sonochemical reactors have potential to be more energy efficient compared to stirred vessel if designed and operated appropriately.